Emotional Intelligence, Spiritual Intelligence, and Academic Achievement in Islamic Religious Education: An Ex Post Facto Study at SMP Negeri 3 Bukittinggi - Febrianda, Febi; Wati, Salmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
This study examined the associations between emotional intelligence, spiritual intelligence, and students’ academic achievement in Islamic Religious Education at SMP Negeri 3 Bukittinggi. A quantitative, nonexperimental approach with an ex post facto design was employed. The population consisted of 510 students in Grades VII, VIII, and IX, from whom 224 respondents were selected through proportional random sampling. Emotional intelligence and spiritual intelligence were measured using two self-report questionnaires, each consisting of 25 items rated on a five-point Likert scale. Academic achievement data were obtained from students’ documented Islamic Religious Education scores. The emotional intelligence scale produced a Cronbach’s alpha coefficient of 0.892, while the spiritual intelligence scale produced a coefficient of 0.967. Data were analyzed using descriptive statistics, bivariate correlation analysis, and multiple linear regression with IBM SPSS Statistics version 25. Emotional intelligence was positively associated with academic achievement, r=0.335, r2=0.112, p<.001. Spiritual intelligence was also positively associated with academic achievement, r=0.339, r2=0.115, p<.001. When considered jointly, the two predictors were significantly associated with academic achievement, R=0.502, R2=0.252, F(2,221)=37.26, p<.001. The findings indicate that emotional and spiritual intelligence are relevant to students’ academic performance, although most of the variation in achievement remained associated with factors outside the model.